Exploring the meaning and interpretations of the proverb "lebitla la mosadi ke bogadi" and its implications on indigenous African women's health : a phenomenological study - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.